BIOLOGY OF HILSA ILISHA (HAMILTON) FROM THE CHILKA LAKE WITH AN ACCOUNT ON ITS RACIAL STATUS - Ramakrishnaiah, M (Indian Journal of Fisheries, 2011)
Hilsa ilisha, known locally as ’ilish’, forms an important commercial fishery in the Chilka lake. Chaudhuri (1916) observed the occurrence of the fish in ths lake throughout the year, Jones and Sujansingani (1951) tentatively concluded from their study of hilsa fishery of the lake that inflow of water from the Daya river influences the fishery; greater flow of flood water inducing large number of spawning fish to migrate. They also reported that Chilka hilsa breeds in the lower reaches of Daya river